Analisis Yuridis Perkawinan Tanpa Pencatatan dalam Perspektif Hukum Islam di Indonesia - Husnan Asidiq (Program Studi Hukum Keluarga Islam (HKI) dan bekerjasama dengan Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Pesantren Sunan Drajat Lamongan, 2026)
This study aims to analyze juridically unregistered marriages from the perspective of Islamic law in Indonesia. This research employs a normative legal method with a library research approach, utilizing primary and secondary legal sources, which are then analyzed qualitatively. The results indicate that in classical Islamic law, the validity of marriage is determined by the fulfillment of its pillars and conditions, without requiring administrative registration. However, in the context of modern Indonesian law, marriage registration holds a significant position as regulated in Law Number 1 of 1974 and the Compilation of Islamic Law. Through the approaches of qiyas, sadd adz-dzari’ah, and mashlahah mursalah, marriage registration can be understood as an effort to achieve public benefit and to provide legal certainty and protection for husbands, wives, and children. Unregistered marriages lead to various legal consequences, particularly for women and children, such as lack of legal recognition, difficulties in obtaining inheritance rights, and weak legal protection. Therefore, marriage registration can be considered an essential legal necessity and is relevant to be incorporated as part of strengthening the pillars of marriage within the framework of Islamic law in Indonesia.